Pengaruh Konseling Kelompok Menggunakan Pendekatan Cognitive Behavior Therapy untuk Meningkatkan Kontrol Diri Siswa - Emeliya Hardi; Desi Ermayulis; Masril Masril (Institut Agama Islam Negeri Kerinci, Indonesia, 2019)
The main problem in this study is the lack of self-control of students in class XI IPS SMAN 1 Batipuh. The purpose of this study was to see how much influence the group counseling approach to Cognitive Behavior Therapy to improve self-control of students of class XI IPS SMAN 1 Batipuh. This type of research is quantitative research using experimental methods. The design used in this study was pre-experimental design with the type of one group pretest-posttest design, namely by measuring the self-control of the experimental group students by using the same instrument in the pretest and posttest measurements. The population in this study were all students of class XI IPS SMAN 1 Batipuh, the sample in this study were 10 students who have low self-control. The results showed that cognitive behavior therapy approach group counseling had a significant effect on student self control. This can be seen based on the results of